Preparation method and application of solid-liquid dual-phase positive electrode material
Patent Information
- Application Number
- CN202411378601.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Due to the low conductivity and volume changes of sulfur, lithium-sulfur batteries have low utilization rate, poor circulation stability and low Coulomb efficiency, which hinder their development.
Using the preparation method of solid-liquid biphasic positive electrode materials, the S-X bonds are formed in the electrochemical process through organic sulfur polymer and organic small molecule ether, and the high electron conductivity of selenium or tellurium elements are introduced to enhance the electron conductivity, and small molecules in the liquid phase are passed through The anchoring and functional functional groups improve the utilization rate and conversion ability of active substances.
It achieves high reaction kinetics, long cycle performance and stable capacity performance, simplifies the preparation process and facilitates large-scale application.
Smart Images

Figure CN119297279A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a preparation method and application of a solid-liquid dual-phase positive electrode material. Background Art
[0002] Sulfur has become an ideal material for new electrochemical energy storage devices due to its abundant reserves, environmental friendliness and high theoretical capacity (1675 mAh / g). Lithium-sulfur batteries constructed with sulfur as the positive electrode and lithium metal as the negative electrode have a much higher theoretical energy density than lithium-ion batteries (2600 Wh / kg). However, sulfur has poor intrinsic conductivity and will produce a shuttle effect during discharge. At the same time, the large volume change during charging and discharging will lead to problems such as reduced utilization of active materials, poor cycle stability and low coulombic efficiency, which seriously hinders the development of lithium-sulfur batteries. At present, physical confinement, chemical adsorption and catalytic effects are mostly used to improve reaction kinetics and inhibit the shuttle effect. However, the introduction of inactive materials will affect the energy density of the battery.
[0003] Organic sulfur materials composed of carbon, hydrogen, and sulfur elements have mild preparation conditions and controllable structures, making them highly promising cathode materials. By regulating the carbon skeleton, sulfur chain, and functional functional groups, the structure, voltage platform, and reaction path of organic sulfur materials can be changed. At the same time, the controllable sulfur chain can inhibit the shuttle effect. The relatively high sulfur content of sulfur-containing polymers gives them a higher theoretical capacity than small molecule structures, but due to the intrinsic properties of sulfur-containing polymers (poor electronic conductivity, poor kinetics, etc.), faster reaction kinetics cannot be achieved. Compared with organic sulfur polymer materials, organic selenium and organic tellurium polymer materials in the same main group as sulfur have higher ionic and electronic conduction, but the preparation conditions are harsh and it is difficult to achieve large-scale application.
[0004] Therefore, by applying organic sulfur compounds and molecules of the same main group to the same system, and utilizing their interactions in the electrochemical process to in-situ cross-link sulfur and atoms of the same main group such as selenium and tellurium, organic sulfur polymers containing selenium and tellurium can be constructed, which can effectively increase the electronic conductivity of organic sulfur compounds, enhance the capacity of electrode materials, and achieve long cycle performance. At the same time, this method is simple, feasible, and easy to apply on a large scale. Therefore, constructing a suitable organic sulfur cathode system helps to promote the electrochemical reaction kinetics and improve the electrochemical performance of lithium batteries. Summary of the invention
[0005] The object of the present invention is to provide a solid-liquid dual-phase positive electrode material for use in lithium batteries. The solid-phase positive electrode active material and the liquid-phase active material undergo cross-linking of active segments during the charge and discharge process, forming SX bonds in situ (X is a sulfide element such as selenium or tellurium). Through the formation of SX bonds, elements with high electronic conductivity are introduced into the organic sulfur polymer skeleton, which improves the electronic conductivity of the organic sulfur polymer while providing electrochemical capacity. At the same time, organic small molecule ethers with high solubility in the liquid phase are anchored on the positive electrode side due to the formation of SX bonds, which reduces the dissolution and loss of active substances and improves the utilization rate. At the same time, the introduction of inactive functional groups also helps to improve the conversion capacity of active substances.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a solid-liquid dual-phase positive electrode material comprises the following steps: Step (1), using an organic sulfur polymer as a solid phase sulfur positive electrode of a solid-liquid dual phase positive electrode material; using an organic small molecule ether as a liquid phase positive electrode of a solid-liquid dual phase positive electrode material; Step (2), in the battery structure, the positive electrode side is a solid-phase sulfur positive electrode, and the electrolyte part is a liquid-phase positive electrode, thereby obtaining a solid-liquid dual-phase positive electrode material.
[0007] Furthermore, in the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material, the organic sulfur polymer in step (1) is a sulfur-rich polymer having a "solid-liquid-solid" or "solid-solid" electrochemical reaction, including poly(sulfur-indole-1, 3-diisopropenylbenzene), polypropylene sulfide or sulfide polyacrylonitrile.
[0008] Furthermore, in the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material, the organic small molecule ether in step (1) is one or more of diphenyl diselenide, dimethyl diselenide, dibenzyl diselenide, diethyl diselenide, bis(aminophenyl) diselenide, biphenyl ditelluride, or diphenyl ditelluride.
[0009] Furthermore, in the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material, the organic small molecule ether in step (1) is soluble in the ether electrolyte and exists stably, and the ether bond exerts electrochemical capacity through the bond breaking / bonding process during the charge and discharge process.
[0010] Furthermore, in the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material, the organic small molecule ether in step (1) contains a conjugated structure, including but not limited to a phenyl group.
[0011] Furthermore, in the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material, in step (2), the sulfur / X atomic ratio of the organic sulfur polymer and the organic small molecule ether is (1-10): 1, wherein X is Se or Te element; the active segments of the organic sulfur polymer and the organic small molecule ether are cross-linked during the electrochemical reaction, thereby changing the structure and electrochemical properties of the active substance.
[0012] Furthermore, in the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material, the concentration of the organic small molecule ether in the electrolyte in step (2) is (10-1000) mmol / L.
[0013] Furthermore, in the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material, in step (2), the organic small molecule ether is dripped into the positive electrode sheet during the battery assembly process.
[0014] Furthermore, in the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material, in step (1), the solid-phase sulfur positive electrode is loaded in a positive electrode current collector, and the current collector includes but is not limited to a carbon-coated aluminum foil or a self-supporting current collector.
[0015] Application of the solid-liquid dual-phase positive electrode material prepared by the above-mentioned method for preparing a solid-liquid dual-phase positive electrode material in lithium batteries.
[0016] The principle of the present invention is as follows: First, a solid-phase organic sulfur polymer is synthesized and loaded on the positive electrode current collector as the solid-phase positive electrode in the solid-liquid dual-phase positive electrode system. Secondly, a certain concentration of organic small molecule ether is dissolved in a commercial ether electrolyte or added to the positive electrode during the battery assembly process as the liquid-phase positive electrode in the solid-liquid dual-phase positive electrode system. The two are combined to form a solid-liquid dual-phase positive electrode system.
[0017] The two-phase active material undergoes cross-linking of active segments during the electrochemical process, forming SX bonds in situ on the positive electrode side. The formation of SX bonds introduces other elements of the same main group into the organic sulfur skeleton of the solid-phase positive electrode, improves electronic conductivity, reduces ohmic impedance, and promotes reaction kinetics. At the same time, other active segments can provide capacity. SX bonds can anchor small organic molecule ethers dissolved in the electrolyte on the positive electrode side, promote reactions, and increase their utilization. Functional groups or conjugated structures in the solid-liquid two-phase active materials can also promote their reaction kinetics and accelerate electrochemical conversion. Therefore, the solid-liquid two-phase positive electrode system has high reaction kinetics, high capacity, and stable long-cycle characteristics.
[0018] Advantages and beneficial effects of the present invention: 1. The solid-liquid dual-phase cathode material prepared by the present invention improves the conductivity and reaction kinetics of the solid phase organic sulfur polymer through the cross-linking effect of the active chain segments, and promotes the reaction activity of small molecules in the liquid phase and the utilization rate of active substances.
[0019] 2. The solid-liquid dual-phase positive electrode material prepared by the present invention promotes the cycle stability and capacity through the interaction of the two-phase active substances.
[0020] 3. The electron-withdrawing groups such as functional groups or conjugated structures contained in the solid and liquid active materials of the present invention can reduce the lowest unoccupied molecular orbital (LUMO) energy level of the active materials and promote the conversion reaction of the active materials in the positive electrode.
[0021] 4. The preparation process of the present invention is simple, the raw materials required for the preparation are widely available, and it can be used for large-scale production.
[0022] 5. The cathode system of the present invention is extensive, and a diversified dual-phase cathode system can be realized by using different types of organic sulfur polymers and organic small molecules soluble in electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the electrochemical performance diagram of the benzoquinone-based polytetrasulfide propane (BTP) solid-phase positive electrode; In the figure: (a) at 1 mA cm -2 First cycle charge and discharge curves at current density; (b) at 1 mA cm -2 Surface capacity-cycle number and coulombic efficiency-cycle number curves under current density; Figure 2 This is the electrochemical performance diagram of diphenyl diselenide (DPhDSe) liquid cathode; In the figure: (a) at 1 mA cm -2 First cycle charge and discharge curves at current density; (b) 1 mA cm -2 Surface capacity-cycle number and coulombic efficiency-cycle number curves under current density; Figure 3 The electrochemical performance diagram of the solid-liquid dual-phase cathode; In the figure: (a) at 1 mA cm -2 First cycle charge and discharge curves at current density; (b) at 1 mA cm -2 Surface capacity-cycle number and coulombic efficiency-cycle number curves under current density; Figure 4 It is a comparison between the solid-liquid dual-phase cathode and the sum of the electrochemical capacities of the two active materials in the system; The black curve in the figure is at 1 mA cm -2 The surface capacity-cycle number curve of the solid-liquid dual-phase cathode battery under the current density; the blue curve is at 1mA cm -2 The sum of the surface capacity per cycle of BTP and DPhDSe batteries under current density-cycle number curve; Figure 5 At 2 mA cm -2 The surface capacity-cycle number and coulombic efficiency-cycle number curves of solid-liquid dual-phase cathode battery cycle under current density; Figure 6 Electrochemical performance diagram of solid-liquid dual-phase cathode battery under high BTP loading condition; In the figure: (a) at 10 mg BTP cm -2 When the loading is 2 mA cm -2 The first cycle charge and discharge curve of the battery at a current density of 2 mA cm -2 The surface capacity-cycle number and coulombic efficiency-cycle number curves of battery cycling under current density; Figure 7 When the solid-liquid dual-phase positive electrode reaches the charged state (2.8V) after 10 cycles, the BTP solid phase positive electrode is at 200-800cm -1 Raman characterization in the range. DETAILED DESCRIPTION
[0024] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples. Example 1
[0025] The present embodiment provides a solid-liquid dual-phase positive electrode material, using benzoquinone-based polytetrasulfide propane (BTP) prepared by interfacial polymerization in an aqueous phase as the solid-phase positive electrode part of the solid-liquid dual-phase positive electrode, and using a lithium-sulfur battery electrolyte containing DPhDSe as the liquid-phase positive electrode in the solid-liquid dual-phase positive electrode system.
[0026] The process of preparing BTP is divided into three steps: the first step is to mix sodium sulfide nonahydrate (Na2S·9H2O) and sulfur powder in an aqueous phase at a molar ratio of 1:3 to generate a sodium tetrasulfide solution; the second step is to mix trichloropropane (TCP) and dichlorobenzoquinone (DCBQ) at a molar ratio of 0.01 to prepare a TCP solution containing DCBQ; the third step is to add the sodium tetrasulfide aqueous solution and the DCBQ TCP solution generated by the reaction at a molar ratio of 0.5 to an aqueous solution containing 20mmol / L CTAB and continue stirring. BTP is finally obtained after more than 12 hours of reaction. The S content in BTP is about 60%. The washed and dried BTP is mixed with the conductive additive and the binder in a ratio of 7:2:1, and evenly coated on the surface of the carbon-containing aluminum foil current collector. After drying, the BTP electrode is obtained, and the BTP loading is about 2mg / cm 2 .
[0027] 500mmol / L DPhDSe was dissolved in the lithium-sulfur battery electrolyte to obtain the cathode solution. The lithium-sulfur battery electrolyte was a mixed solution of DOL and DME (volume ratio 1:1) containing 1M LiTFSI electrolyte and 0.2M LiNO3 additive.
[0028] The positive electrode described in this example was used for electrochemical performance testing in a lithium battery, and a 2025 button cell was used for the electrochemical performance testing of the electrode material: the BTP positive electrode was cut into a circular shape with a diameter of 10 mm as the working electrode, a lithium sheet (diameter 16 mm, thickness 0.45 mm) was used as the counter electrode, and a Celgard 2400 polypropylene film (diameter 19 mm) coated with rGO was used as the separator. The electrolyte was the DPhDSe positive electrode solution configured as above, and the addition amount was 30 μl. The sulfur / selenium atomic ratio of the organic sulfur polymer and the organic small molecule ether is 1:1. During the discharge test, the potential range was 1.7-2.8V (vs. Li / Li + ).like Figure 3 (a) shows that the solid-liquid biphase cathode is at 1 mA cm -2 The first cycle discharge capacity at the current density is 1.38 mAh / cm -2 , the polarization voltage, i.e. the difference between the charging voltage platform and the discharging voltage platform, is small, about 0.15V. Figure 3 As shown in (b), the solid-liquid dual-phase cathode maintains 1.07 mAh / cm after 400 cycles. -2 The average capacity decay rate per cycle is 0.024%. This shows that the synergistic effect of the solid-liquid dual-phase positive electrode system helps to improve the reaction kinetics of lithium batteries, thereby improving the actual capacity and promoting the overall cycle stability of the battery. At the same time, in order to further reflect the synergistic effect of the solid-liquid dual-phase positive electrode system, the electrochemical performance in this embodiment is compared with the two comparative examples. Figure 4 As shown in the figure: In the 400 cycles, the surface capacity of the solid-liquid dual-phase positive electrode is always higher than the sum of the surface capacity of the positive electrodes in the two comparisons. Therefore, the capacity improvement is the result of the interaction between the solid phase organic sulfur polymer and the liquid phase organic small molecule ether in the electrochemical process, rather than the superposition of the electrochemical capacity of the two active substances themselves.
[0029] In addition, a long cycle test was also performed on the battery in this embodiment. Figure 5 As shown, the solid-liquid biphase cathode is at 2 mA cm -2 The first cycle discharge capacity at the current density is 0.82 mAh / cm -2 After 1700 cycles, it maintained 0.46 mAh / cm -2 The average capacity decay rate per cycle is 0.026%. This shows that the synergistic effect of the solid-liquid dual-phase cathode system helps to improve the reaction kinetics of lithium batteries and promote the overall cycle stability of batteries.
[0030] The solid phase positive electrode in this example was prepared with a diameter of 10 mm and a BTP loading of about 10 mg / cm 2 The circular positive electrode sheet was prepared by changing the amount of positive electrode solution added in this embodiment to 90 μl, and the electrochemical test was performed. The sulfur / selenium atomic ratio of the organic sulfur polymer and the organic small molecule ether was 10:3. Figure 6 (a) shows that the solid-liquid biphase cathode is at 2 mA cm -2 The first cycle discharge capacity at the current density is 11.39 mAh / cm -2 , the polarization voltage, i.e. the difference between the charging voltage platform and the discharging voltage platform, is small, about 0.2V. Figure 6 As shown in (b), the high-load solid-liquid dual-phase cathode maintains 7.69 mAh / cm after 25 cycles. -2 This shows that the synergistic effect of the solid-liquid dual-phase cathode system helps to improve the reaction kinetics of lithium batteries and enhance the actual capacity.
[0031] Comparative Example 1 In this comparative example, benzoquinone-based polytetrasulfide (BTP) prepared by interfacial polymerization in water phase is used as a positive electrode material for a lithium battery.
[0032] The process of preparing BTP is divided into three steps: the first step is to mix sodium sulfide nonahydrate (Na2S·9H2O) and sulfur powder in an aqueous phase at a molar ratio of 1:3 and stir to react to generate a sodium tetrasulfide solution; the second step is to mix trichloropropane (TCP) and dichlorobenzoquinone (DCBQ) at a molar ratio of 0.01 to prepare a TCP solution containing DCBQ; the third step is to add the sodium tetrasulfide aqueous solution and the DCBQ TCP solution generated by the reaction at a molar ratio of 0.5 to an aqueous solution containing 20mmol / L CTAB and continue stirring. BTP is finally obtained after more than 12 hours of reaction. The washed and dried BTP is mixed with a conductive additive and a binder in a ratio of 7:2:1, and evenly coated on the surface of the carbon-containing aluminum foil current collector. After drying, a BTP electrode is obtained, and the BTP loading is about 2mg / cm 2 .
[0033] The solid phase organic sulfur polymer of this comparative example was subjected to electrochemical performance test in a lithium-sulfur battery, and a 2025 button battery shell was used to assemble the electrode material for electrochemical performance test. The BTP positive electrode was cut into a disc with a diameter of 10 mm as the working electrode, a lithium sheet (diameter 16 mm, thickness 0.45 mm) was used as the counter electrode, and a Celgard 2400 polypropylene film (diameter 19 mm) coated with reduced graphene oxide (rGO) was used as the diaphragm. The electrolyte was a mixed solution of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (volume ratio 1:1) containing 1M lithium bistrifluoromethanesulfonyl imide (LiTFSI) electrolyte and 0.2M lithium nitrate (LiNO3) additive. During the discharge test, the potential range was 1.7-2.8V (vs. Li / Li + ).like Figure 1 (a) shows that the BTP cathode is at 1 mA cm -2 The first cycle discharge capacity at the current density is 0.74 mAh / cm -2 , the polarization voltage, i.e. the difference between the charging voltage platform and the discharging voltage platform, is relatively large, about 0.3V. Figure 1 As shown in (b), the BTP cathode maintains 0.57 mAh / cm after 400 cycles. -2 The surface capacity of the battery is 0.058% on average per cycle.
[0034] Comparative Example 2 This comparative example uses DPhDSe added to the lithium-sulfur battery electrolyte as the lithium battery positive electrode solution.
[0035] Dissolve 500mmol / L DPhDSe in the lithium-sulfur battery electrolyte to obtain the cathode solution. The lithium-sulfur battery electrolyte is a mixed solution of DOL and DME (volume ratio 1:1) containing 1M LiTFSI electrolyte and 0.2M LiNO3 additive. Mix the conductive additive and the binder in a ratio of 9:1, evenly coat the surface of the carbon-containing aluminum foil current collector, and obtain a pure carbon electrode after drying.
[0036] The electrochemical performance of the liquid organic small molecule ether in this comparative example in a lithium battery was tested, and a 2025 button cell was used as the cathode liquid for electrochemical performance testing. The pure carbon electrode was cut into a circular shape with a diameter of 10 mm as the current collector, a lithium sheet (diameter 16 mm, thickness 0.45 mm) was used as the counter electrode, and a Celgard 2400 polypropylene film (diameter 19 mm) coated with rGO was used as the diaphragm. The electrolyte was the DPhDSe cathode liquid configured above. During the discharge test, the potential range was 1.7-2.8 V (vs. Li / Li + ).like Figure 2 (a) shows that the DPhDSe cathode is at 1 mA cm -2The first cycle discharge capacity at the current density is 0.33 mAh / cm -2 , the polarization voltage, i.e. the difference between the charging voltage platform and the discharging voltage platform, is small, about 0.1V. Figure 2 As shown in (b), DPhDSe maintains 0.24 mAh / cm after 400 cycles. -2 The surface capacity of the battery is 0.069% on average per cycle.
[0037] Therefore, based on the above description, it can be seen that the present invention provides a method for preparing a solid-liquid dual-phase positive electrode material, which can effectively improve the electrochemical kinetics and cycle stability of the positive electrode of a lithium battery. The capacity of "1+1>2" is achieved through the cross-linking of active segments under the two phases, and has higher capacity and cycle performance under long cycles and high solid-phase active material loading. The preparation method of this patent is simple, highly repeatable, highly flexible in material selection, easy to control, and has broad application prospects.
[0038] The above description is only a preferred embodiment of the present invention. It should be pointed out that the above embodiments are illustrative in nature and cannot be understood as limitations of the present invention. Several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a solid-liquid dual-phase cathode material, characterized in that: The steps include: Step (1), using an organic sulfur polymer as a solid phase sulfur positive electrode of a solid-liquid dual phase positive electrode material; using an organic small molecule ether as a liquid phase positive electrode of a solid-liquid dual phase positive electrode material; Step (2), in the battery structure, the positive electrode side is a solid-phase sulfur positive electrode, and the electrolyte part is a liquid-phase positive electrode, thereby obtaining a solid-liquid dual-phase positive electrode material.
2. The method for preparing a solid-liquid dual-phase cathode material according to claim 1, characterized in that: The organic sulfur polymer in step (1) is a sulfur-rich polymer having a "solid-liquid-solid" or "solid-solid" electrochemical reaction, including poly(sulfur-indole-1,3-diisopropenylbenzene), polypropylene sulfide or polyacrylonitrile sulfide.
3. The method for preparing a solid-liquid dual-phase cathode material according to claim 1, characterized in that: In step (1), the organic small molecule ether is one or more of diphenyl diselenide, dimethyl diselenide, dibenzyl diselenide, diethyl diselenide, bis(aminophenyl) diselenide, biphenyl ditelluride, or diphenyl ditelluride.
4. The method for preparing a solid-liquid dual-phase cathode material according to claim 3, characterized in that: In step (1), the organic small molecule ether is soluble in the ether electrolyte and exists stably. During the charge and discharge process, the ether bond exerts electrochemical capacity through the bond breaking / bonding process.
5. The method for preparing a solid-liquid dual-phase cathode material according to claim 3, characterized in that: The organic small molecule ether in step (1) contains a conjugated structure, including but not limited to a phenyl group.
6. The method for preparing a solid-liquid dual-phase cathode material according to claim 1, characterized in that: In step (2), the sulfur / X atomic ratio of the organic sulfur polymer and the organic small molecule ether is (1-10): 1, wherein X is Se or Te element; the active chain segments of the organic sulfur polymer and the organic small molecule ether are cross-linked during the electrochemical reaction, thereby changing the structure and electrochemical properties of the active substance.
7. The method for preparing a solid-liquid dual-phase cathode material according to claim 1, characterized in that: In step (2), the concentration of the organic small molecule ether in the electrolyte is (10-1000) mmol / L.
8. The method for preparing a solid-liquid dual-phase cathode material according to claim 1, characterized in that: In step (2), the organic small molecule ether is added dropwise to the positive electrode sheet during the battery assembly process.
9. The method for preparing a solid-liquid dual-phase cathode material according to claim 1, characterized in that: In step (1), the solid-phase sulfur positive electrode is loaded in the positive electrode current collector, and the current collector includes but is not limited to carbon-coated aluminum foil or a self-supporting current collector.
10. Use of the solid-liquid dual-phase positive electrode material prepared by the method for preparing a solid-liquid dual-phase positive electrode material according to any one of claims 1 to 9 in a lithium battery.
Citation Information
Patent Citations
Preparation method of polymer positive electrode material for lithium-sulfur b]attery
CN113140710A
Preparation method of organic sulfur polymer positive electrode for lithium-sulfur battery
CN116435470A
Solid-phase conversion sulfur positive electrode, preparation method thereof and lithium-sulfur battery
CN116936736A